TiO2 composite electrode materials for lithium batteries. (20th January 2021) - Pidluzhna, Anna
Abstract: The search of new practical solutions in electrode fabrication process is important branch among all directions in the field of lithium batteries. This study presents the investigation results of electrochemical behaviour of lithium elements with composite electrodes made from nano TiO2, polypropylene as a binder material, carbon black as a conductive additive. Scanning electron microscopy and X-ray photoelectron spectroscopy were used for material characterisation. Cyclic voltammetric tests were conducted for investigation of electrochemical behaviour of nano TiO2 composite electrodes and electrochemical properties of these electrodes are described in this study. Graphical abstract: Image, graphical abstract